Cybersecurity in unmanned aerial vehicles (UAVs). Issue 2 (3rd April 2021) - Ly, Bora; Ly, Romny
ABSTRACT: For the investigation, the security factor is crucial as Unmanned Aerial Vehicles (UAVs) become prevalent, and their operational range grows exponentially. This research is a comprehensive literature review investigating which cyber-attacks are most frequent and what consequences they cause in civilian UAV attacks. The cyber threats described in this study are categorized using the STRIDE attack paradigm, the challenge they pose, and the appropriate equipment for the attack. The most common forms of UAV cyberattack and the most effective result are spoofing and denial of service attacks. No difficult-to-reach device is needed for any attack style, meaning that the security state currently requires enhancements to civilian use of UAVs in most cases.